Clinical evolution of post-transplant diabetes mellitus - Esteban Porrini; Jose M. Saz Diaz; Francesc Moreso; Patricia Isabel Delgado Mallén; Irene Silva Torres; Meritxell Ibernón; Beatriz Bayés-Genís; Rocío Benitez-Ruiz; I Lampreabe; Ricardo Lauzurrica; J.M. Osorio; Antonio Osuna; et al. (2015)
The long-term clinical evolution of prediabetes and post-transplant diabetes mellitus (PTDM) is unknown. We analysed, in this cohort study, the reversibility, stability and progression of PTDM and prediabetes in 672 patients using repeated oral glucose tolerance tests (OGTTs) for ≤5 years. Most patients were on tacrolimus, steroids and mycophenolate. About half developed either PTDM or prediabetes. The incidence of PTDM was 32% and bimodal: early PTDM (≤3 months) and late PTDM. Early PTDM reverted in 31%; late PTDM developed in patients with post-transplant prediabetes. The use of OGTTs was necessary to detect around half of PTDM. Pretransplant obesity was a major risk factor for early PTDM, for its persistence and for late PTDM {odds ratio [OR] 1.18 [95% confidence interval (CI) 1.09–1.28]}. At 3 months, higher HbA1c promoted [OR 2.37 (95% CI 1.38–4.06)], while insulin sensitivity protected against [OR 0.64 (95% CI 0.48–0.86)] late PTDM. At 3 months, 28% had prediabetes; of these, 36% remained stable, 43% normalized and 21% developed late PTDM. Pretransplant obesity [OR 1.20 (95% CI 1.04–1.39)] and higher HbA1c [OR 3.80 (95% CI 1.45–9.94)] at 3 months promoted while insulin sensitivity protected against [OR 0.57 (95% CI 0.34–0.95)] evolution from prediabetes to late PTDM. Immunosuppressive levels or acute rejection did not influence PTDM. Most (84%) of the patients with normal tests at 3 months remained stable without evolving into PTDM; 14% developed prediabetes. PTDM and prediabetes are very common in renal transplantation. Classic metabolic factors like obesity, prediabetes and insulin resistance promote the evolution of PTDM and prediabetes. Patients with normal glucose metabolism rarely develop PTDM. OGTT is necessary to detect PTDM and prediabetes and thus should be included in clinical practice.